Where the sidewalk ends : the poems & drawings - Silverstein, Shel. (New York : HarperCollins Publishers, 1974)
A boy who turns into a TV set and a girl who eats a whale are only two of the characters in a collection of humorous poetry illustrated with the author's own drawings.
Includes index.
Book Links (A.L.A.).
Elem. School Library Collection.
Wilson's Junior High School.
Book Links (A.L.A.), May 1995.
Booklist, March 1998.
Keywords: Humorous poetry; Humorous poetry; Humorous poetry